ACCESSIBILITY, RECEPTION AND PROMOTION OF MACEDONIAN LITERATURE IN SLOVENIA (Philological Studies, 2025)
The article addresses the accessibility, reception and promotion of reading Macedonian literature in Slovenia and the need for translated literature by Macedonian authors. The structure of the main section is based on a personal interpretation of the reception of Macedonian literature in Slovenia and covers: a) the accessibility of Macedonian literature, referring to literary translation (between 1947 and 1999 and between 2000 and the data collection in August 2023, overview of translation studies and translation prizes), printed copies (the print run and the proportion allocated for library lending), and electronic and audio editions (between 1947 and 1999 and between 2000 and the data collection in August 2023, and records in the Catalogue of Audio Books of the Minka Skaberne Library for the Blind and Visually Impaired), b) the reception of Macedonian literature, referring to literary-critical contributions (between 2000 and 2023), literary guest appearances at festivals, literary prizes and inclusion in the recommended reading list “DOBREKNJIGE.SI”, and c) the promotion of the reading of Macedonian literature, which is directly related to the reading project “Our Little Library” and the reading club “Slavic Reading Badge” of the Department of Slavistics of the Faculty of Arts of the University of Ljubljana, and indirectly to the activities in the Erasmus+ Programme.
Keywords: Macedonian literature, literary translation, translation studies, translation prizes, recommendation lists, literary criticism